2020
DOI: 10.1093/cid/ciaa620
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Time From Human Immunodeficiency Virus Diagnosis to Care, Antiretroviral Therapy Initiation, and Virologic Suppression during the Citywide RAPID Initiative in San Francisco

Abstract: Background Early virologic suppression after HIV infection improves individual health outcomes and decreases onward transmission. In San Francisco, immediate ART at HIV diagnosis was piloted in 2013-14 and expanded citywide in 2015 in a rapid start initiative to link all new diagnoses to care within five days and start ART at the first care visit. Methods HIV providers and linkage navigators were trained on a rapid start prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…The proportion of new cases that were linked to care and started ART within the RAPID Protocol's timelines was tracked over time, and the association between rapid ART initiation and VS was analyzed. 5 Outcomes were stratified by sex/gender, race/ethnicity, age, transmission category, and housing status to monitor inclusion and outcomes among historically underserved groups.…”
Section: Metrics and Accountabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of new cases that were linked to care and started ART within the RAPID Protocol's timelines was tracked over time, and the association between rapid ART initiation and VS was analyzed. 5 Outcomes were stratified by sex/gender, race/ethnicity, age, transmission category, and housing status to monitor inclusion and outcomes among historically underserved groups.…”
Section: Metrics and Accountabilitymentioning
confidence: 99%
“…The RAPID ART initiatives in San Francisco, both at the Ward 86 clinic and at the citywide level, have shown that immediate initiation of ART after HIV diagnosis can substantially lower time to ART initiation and result in very high rates of VS, even in disproportionately affected populations. 5,6 Based on evidence from U.S. and international rapid ART programs (which used somewhat different timelines for ART start), 1,2,5−8 immediate ART at diagnosis is now recommended by national and international guidelines. 9−11 Prior work reported early outcomes of the San Francisco Citywide RAPID ART initiative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up of the RAPID cohort did show that 95% maintained viral suppression at 1 year [ 25 ]. However, as this approach was adopted by the entire city of San Francisco, a recent evaluation of citywide RAPID outcomes demonstrated that some groups, including Latinx patients, were more likely to initiate iART at first visit, while transgender women were least likely to initiate iART at first visit [ 26 ]. There were also emerging disparities in time to first viral suppression among people who inject drugs and African Americans [ 26 ].…”
Section: The Rapid Model Expansion Of Iart and Health Disparitiementioning
confidence: 99%
“…However, as this approach was adopted by the entire city of San Francisco, a recent evaluation of citywide RAPID outcomes demonstrated that some groups, including Latinx patients, were more likely to initiate iART at first visit, while transgender women were least likely to initiate iART at first visit [ 26 ]. There were also emerging disparities in time to first viral suppression among people who inject drugs and African Americans [ 26 ]. The signal of emerging disparities highlighted by this study calls for an evaluation of what key elements need to be added to the RAPID model to better serve the most vulnerable populations with HIV.…”
Section: The Rapid Model Expansion Of Iart and Health Disparitiementioning
confidence: 99%